2012
DOI: 10.18590/euscorpius.2012.vol2012.iss137.1
|View full text |Cite
|
Sign up to set email alerts
|

Another new sub-fossil species of scorpion of the genus Palaeogrosphus Lourenço, 2000 from Malagasy copal (Scorpiones: Buthidae)

Abstract: Palaeogrosphus jacquesi sp. n., the third known sub-fossil scorpion from Malagasy copal, is described. This is the fourth record of a sub-fossil scorpion in copal. The copal specimen was collected in the mines of the region of Sambava, Province of Antsiranana in the northeast of Madagascar. It belongs to the genus Palaeogrosphus Lourenço, 2000, described from Madagascar, and now represented by two sub-fossil species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…However, other species are known only from their preservation in "copal" [76,135,136], thus it is possible that some of them could be found alive in the Malagasy eastern coastal forests [10,19]. Recently, Riquelme et al [137], after a study of scorpions from Miocene Mexican amber, proposed a phylogeny that included three buthid species found in "Madagascar copal"; one species was assigned to the Recent genus Microcharmus (Microcharmidae) and the rest to undetermined species in the Recent genus Palaeogrosphus [8,136,138]. They suggested that "Malagasy copal" is less than 250 years old (without explanation or new data), and that the species recognised, other than fossil or sub-fossil species, may be considered extant species.…”
Section: Palaeobiological Implications For Previous "Madagascar Copalmentioning
confidence: 99%
“…However, other species are known only from their preservation in "copal" [76,135,136], thus it is possible that some of them could be found alive in the Malagasy eastern coastal forests [10,19]. Recently, Riquelme et al [137], after a study of scorpions from Miocene Mexican amber, proposed a phylogeny that included three buthid species found in "Madagascar copal"; one species was assigned to the Recent genus Microcharmus (Microcharmidae) and the rest to undetermined species in the Recent genus Palaeogrosphus [8,136,138]. They suggested that "Malagasy copal" is less than 250 years old (without explanation or new data), and that the species recognised, other than fossil or sub-fossil species, may be considered extant species.…”
Section: Palaeobiological Implications For Previous "Madagascar Copalmentioning
confidence: 99%
“…Currently the type material of ‘ Tityus’ eogenus is missing [ 12 ]. There are also three buthid species found in the Recent Madagascar copal (less than 250 years old); one species was assigned to the genera Microcharmus (family Microcharmidae) and other two into Palaeogrosphus [ 2 ][ 52 ][ 54 ][ 55 ]. However, these may be considered as extant species, not belonging to the fossil or even subfossil record due to the recent depositional age of copal ( Fig 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…n. Teruelius bemaraha (Lourenço, Wilmé & Waeber, 2018) comb. n. Teruelius bicolor (Lourenço, 2012) comb. n. Teruelius bistriatus (Kraepelin, 1900) comb.…”
Section: Grosphus Hirtus Garciaimentioning
confidence: 99%
“…Neogrosphus may represent a separate founder allied to Parabuthus (an affinity suggested by the oblique V 1 -V 2 trichobothrial axis on the pedipalp chela shared by the two genera). The genus Palaeogrosphus, known from two subfossils of Pleistocene vintage in Malagasy copal (Lourenço, 1996d(Lourenço, , 2000bLourenço & Henderickx, 2012), also shares a character with Parabuthus (enlarged basal middle lamella on female pectines), but its relationship to the 'Grosphus' group is unclear. More recent local rafting events have been suggested as possible mechanisms to explain the presence of Grosphus mayottensis in the Comoros Archipelago (Lourenço & Goodman, 2009), and the widely separated distributions of Teruelius bistriatus and T. waeberi along the west coast (Lourenço & Wilmé, 2016).…”
Section: Biogeographymentioning
confidence: 99%